2020
DOI: 10.1186/s12884-020-03070-z
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for developing, disseminating, and implementing a core outcome set (COS) for childbirth pelvic floor trauma research

Abstract: Background: More than 85% of women sustain different degrees of trauma during vaginal birth. Randomized controlled trials on childbirth pelvic floor trauma have reported a wide range of outcomes and used different outcome measures. This variation restricts effective data synthesis, impairing the ability of research to inform clinical practice. The development and use of a core outcome set (COS) for childbirth pelvic floor trauma aims to ensure consistent use of outcome measures and reporting of outcomes. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…Our methodology for the development of the COS and COMS in cosmetic gynecological interventions will be based on the standards set out by the COS-STAD (Core Outcome Set-Standards for Development) recommendations [ 33 - 35 ]. The COS-STAD recommendations suggest that the development of a protocol at the start of the COS development process is advisable, as it increases transparency of the process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our methodology for the development of the COS and COMS in cosmetic gynecological interventions will be based on the standards set out by the COS-STAD (Core Outcome Set-Standards for Development) recommendations [ 33 - 35 ]. The COS-STAD recommendations suggest that the development of a protocol at the start of the COS development process is advisable, as it increases transparency of the process.…”
Section: Methodsmentioning
confidence: 99%
“…The question regarding ethics has been considered and addressed in a number of previous COS development projects. It has been suggested that these projects are considered a service evaluation not directly influencing patient care or safety [ 26 , 34 , 35 , 37 , 44 ]. Consent will be sought from all participants involved before their participation in either stakeholder interviews or the Delphi survey.…”
Section: Methodsmentioning
confidence: 99%
“…High-quality studies were considered those that reached score ≄ 4 based on these criteria. All assessments were undertaken independently by two assessors in line with our previous studies and similar research [7][8][9][10][11][12]. In cases of disagreement, a third assessor reviewed the scores and provided additional scores.…”
Section: This Review Is Part Of Chorus (An International Collaboration For Harmonizing Outcomes Research and Standards Inmentioning
confidence: 99%
“…Our previous systematic review developed the inventory of reported outcomes and outcomes measures as a first step in the process of developing relevant COS based on established standards and following well-defined study protocols and high-quality methods [6]. Our systematic reviews on outcome reporting in trials evaluating surgical treatments in different prolapse procedures, incontinence and childbirth trauma [5,[7][8][9][10][11][12] included assessments of associations between outcome reporting quality, methodological quality and publication characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main aims of CHORUS is the development and dissemination of Core Outcome Sets in pelvic floor disorders. 4,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] The development and quality of clinical guidelines is usually related to the quality of published evidence, which in turn is associated with the selection and reporting of outcomes and outcome measures. The process of development of core outcome sets is advisable to include guideline developers.…”
Section: Introductionmentioning
confidence: 99%